Legal Politics of Electronic Documents in State Finances As Legal Evidence - Rizky Dian Bareta; Triyono Triyono; Rahmat Rahmat (Jurnal Ilmiah Dunia Hukum, 2023)
Disruption of digital technology as part of the industrial revolution 4.0 forces changes in human culture to keep up with the times, including in public institutions. Regulating the digitalization of state finances has risks, including electronic evidence in court that is very likely to occur, given that corruption in state finances is still rampant, requiring legal evidence in court. This research is normative research by examining the existence of regulations related to electronic documents in state finances and explaining how electronic documents are formed. In this study, it can be concluded that regulations regarding electronic evidence have been adequately accommodated, although there is still an asymmetry in the classification of electronic evidence itself. Regulations governing electronic documents in the field of state finances still refer to laws regarding electronic information and transactions. These regulations are considered complete, although, in several regulations in the field of state finance, adjustments are still required to support the use of electronic documents in state finances. Electronic signatures are divided into certified and uncertified signatures, but certified signatures make the presence of an ideal electronic document. This research can be used as input for policymakers in implementing electronic documents in state finance.